2017
DOI: 10.1002/2017gl074820
|View full text |Cite
|
Sign up to set email alerts
|

On the Dependence of Cloud Feedbacks on Physical Parameterizations in WRF Aquaplanet Simulations

Abstract: We investigate the effects of physical parameterizations on cloud feedback uncertainty in response to climate change. For this purpose, we construct an ensemble of eight aquaplanet simulations using the Weather Research and Forecasting (WRF) model. In each WRF‐derived simulation, we replace only one parameterization at a time while all other parameters remain identical. By doing so, we aim to (i) reproduce cloud feedback uncertainty from state‐of‐the‐art climate models and (ii) understand how parametrizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Regional and local scale precipitation remains challenging to simulate well in large scale dynamical climate models (e.g., Cesana et al, 2017; Tapiador et al, 2019). Accordingly, impacts researchers benefit from using SD‐generated precipitation projections as input to their work, as long as the sensitivities of precipitation‐related variables connected to their needs are better documented.…”
Section: Introductionmentioning
confidence: 99%
“…Regional and local scale precipitation remains challenging to simulate well in large scale dynamical climate models (e.g., Cesana et al, 2017; Tapiador et al, 2019). Accordingly, impacts researchers benefit from using SD‐generated precipitation projections as input to their work, as long as the sensitivities of precipitation‐related variables connected to their needs are better documented.…”
Section: Introductionmentioning
confidence: 99%
“…We perform simulations using the global WRF model (ARW, Version 3) (Skamarock et al, 2008) in aquaplanet setup (Hoskins et al, 1999). This setup has also been utilized in Bhattacharya et al (2017), as well as in Cesana et al (2017). The horizontal resolution is 1 31 and we use a stretched vertical mesh with 40 levels up to the top of the atmosphere.…”
Section: Setupmentioning
confidence: 99%
“…Here we investigate how different boundary layer and convection parameterizations interact with each other in a global model and how they produce different mean-state climates. As suggested by a number of recent studies (Cesana et al, 2017;Medeiros et al, 2008Medeiros et al, , 2015Medeiros et al, , 2016Stevens & Bony, 2013), aquaplanet simulations provide an attractive framework for these investigations, as they retain the dynamics and physics of fully realistic simulations, but eliminate complexities arising from land surface, topography, and other zonal asymmetries. In addition, lack of long timescale processes associated with the ocean circulation and land implies that a shorter spin-up is required to reach equilibrium of the generated climate (Williamson et al, 2012), making it computationally more feasible to perform numerous simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of the WRF is constructed by many different parameterizations for each physical scheme, such as radiation, microphysics (MP), convection or cumulus (CU), and planetary boundary layer (PBL). Therefore, thousands of combinations can be generated (Cesana et al ., 2017). Previous studies have shown that different combined physical parameterizations have different performances in regional climate simulations (Jankov et al ., 2005; Misenis and Zhang, 2010; Osuri et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%